2014
DOI: 10.1111/jocn.12544
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the initiation of an exercise programme on seroma formation and dehiscence following breast cancer surgery

Abstract: Studies showing evidence that early functional rehabilitation process is a safe practice for women having surgery for breast cancer, as well as the present research, are of interest to health professionals who care for these patients and contribute to the wider global clinical community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 18 publications
0
11
0
1
Order By: Relevance
“…Most studies (39 of 57) were RCT [ 19 57 ], five were controlled non randomized clinical trials [ 58 63 ], four were prospective cohort studies [ 61 , 64 66 ], one was a retrospective cohort study [ 67 ], two was a case–control study [ 68 , 69 ], four were quasi-experimental [ 70 – 73 ], one was a pilot study [ 74 ] and one was a feasibility study [ 75 ]. The studies originated from 22 countries distributed across 4 continents (i.e., Americas, Europe, Asia and Oceania), most of which were high income countries [ 19 26 , 29 , 31 , 33 – 36 , 39 41 , 44 47 , 50 , 52 54 , 56 , 57 , 59 , 61 – 69 , 71 , 73 75 ] or upper-middle income countries [ 27 , 28 , 30 , 32 , 37 , 38 , 42 , 43 , 48 , 49 , 58 , 60 , 72 ], with only three studies conducted in lower-middle income countries [ 51 , 55 , 70 ]. The body of literature on this topic turned out to be quite recent, with 71.9% (41 of 57) of studies published between 2010 and 2022 and 22.8% (13 out of 57) between 2000 and 2009.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies (39 of 57) were RCT [ 19 57 ], five were controlled non randomized clinical trials [ 58 63 ], four were prospective cohort studies [ 61 , 64 66 ], one was a retrospective cohort study [ 67 ], two was a case–control study [ 68 , 69 ], four were quasi-experimental [ 70 – 73 ], one was a pilot study [ 74 ] and one was a feasibility study [ 75 ]. The studies originated from 22 countries distributed across 4 continents (i.e., Americas, Europe, Asia and Oceania), most of which were high income countries [ 19 26 , 29 , 31 , 33 – 36 , 39 41 , 44 47 , 50 , 52 54 , 56 , 57 , 59 , 61 – 69 , 71 , 73 75 ] or upper-middle income countries [ 27 , 28 , 30 , 32 , 37 , 38 , 42 , 43 , 48 , 49 , 58 , 60 , 72 ], with only three studies conducted in lower-middle income countries [ 51 , 55 , 70 ]. The body of literature on this topic turned out to be quite recent, with 71.9% (41 of 57) of studies published between 2010 and 2022 and 22.8% (13 out of 57) between 2000 and 2009.…”
Section: Resultsmentioning
confidence: 99%
“…Nearly half of rehabilitation interventions (47.4%) were delivered using a mixed approach, initially performed under nursing staff or physical therapists' supervision and, in most instances, transitioned to a home-based intervention upon hospital discharge. Home-based interventions (15.8%) all consisted of exercises, which were either performed alone [ 38 , 43 , 68 , 72 ], combined with patient education [ 36 , 56 , 64 , 74 ] or with manual therapy [ 63 ]. Six studies reported implementing group interventions consisting solely of supervised exercise programs [ 30 , 41 , 49 , 55 , 60 ] or exercise combined with manual therapy [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Одни авторы отмечают снижение объемов лимфореи у больных, которым выполнялась иммобилизация руки в положении приведения на стороне операции [9]. Дру-гие авторы, проведя рандомизированное исследование 77 больных [10] и метаанализ [11], установили, что ста-тистически значимой разницы в части формирования серомы между ранним и поздним началом ЛГ нет. Это подтверждает и наш опыт наблюдения за вышеуказан-ными 1447 больными -раннее начало гимнастических упражнений не влияет на величину и длительность лимфореи и на наличие расхождения краев раны.…”
Section: таблица 2 примерный комплекс лечебно-гимнастических упражнеunclassified
“…Bovine thrombin, fibrin glue, and steroids all demonstrated to be ineffective in reducing seroma 10–12 . Inconsistent results were reported for shoulder immobilisation and external compression 13–15 . One of the key factors in reducing seroma formation seems mechanical closure of the dead space left after surgery 6,16 .…”
Section: Introductionmentioning
confidence: 99%
“… 10 , 11 , 12 Inconsistent results were reported for shoulder immobilisation and external compression. 13 , 14 , 15 One of the key factors in reducing seroma formation seems mechanical closure of the dead space left after surgery. 6 , 16 The quilting suture technique, where dead space left after surgery is minimised by fixation of the skin flaps to the underlying muscle, was reported to significantly reduce seroma incidence in several studies.…”
Section: Introductionmentioning
confidence: 99%